PERBEDAAN KADAR ASAM FOLAT SERUM PENDERITA ABORTUS SPONTAN DENGAN KEHAMILAN NORMAL - Ermawati, Ermawati; Bachtiar, Hafni (Fakultas Kedokteran Universitas Andalas, 2018)
Abortion is the termination of pregnancy before fetus can survive in the outside world, regardless of the cause. One cause of spontaneous abortion due to maternal nutritional factors, such as folic acid defi-ciency, lead to disruption of cell function and ends with apoptosis as well as continuing with fetal death. The study was conducted to determine differences in the levels of folic acid serum between patients with normal pregnancy and spontaneous abortion in some hospitals in West Sumatra. The study was con-ducted by the method of analytic observational comparative cross-sectional design. This research was carried out on pregnant women who come to the clinic and emergency obstetric Dr.M.Djamil hospital Padang, Batusangkar Hospital, Reksodiwiryo Hospital Padang and examinations conducted in biomed-ical laboratory medical faculty Andalas University the period August-December 2014. The total number of women included in the statistical calculation after the inclusion and exclusion criteria are met is 54 people, statistical analysis was done afterwards. The mean levels of serum folic acid is lower in sponta-neous abortion patients compared with average levels of folic acid in normal. Results of statistical anal-ysis using t-test found significant differences in the mean serum levels of folic acid group of spontaneous abortion patients with normal pregnancy group, it can be seen from p-value 0.001 (p <0.05).Keywords: Spontaneous abortion, folic acid, fetus death